Shape Loss of Autoclaved, Machine-Bent Cobalt-Chrome and Titanium Spine Surgery Rods. Issue 4 (May 2021) - Willson, Rob; Zhou, Haitao; Fulzele, Sadanand; Mitchell, Sean M.; Chutkan, Norman
Study Design: This was a biomechanical study. Objective: Shape loss of surgical spine rods has been implicated as a factor leading to postsurgical loss of alignment correction. Our objective was to compare the degree of shape loss in surgical spine rods of different compositions under physiological conditions that were bent before or after being autoclaved. Methods: 10 CoCr and 10 commercially pure titanium (CPTi) surgical spine rods were contoured using a machine press. Five CoCr and 5 CPTi rods were bent before being autoclaved (preoperative bent group); 5 CoCr and 5 CPTi rods were bent after being autoclaved (intraoperative bent group). All rods were immersed in a phosphate-buffered saline bath at body temperature (37.2°C ± 2°C). Changes in radius of curvature were measured at different time intervals over an 8-week course using a high-definition scanner. Results: Each rod demonstrated shape loss in radius of curvature (range = 1.04-9.99 mm) over the duration of the study. Intraoperatively bent CPTi rods demonstrated the largest shape loss (range = 8.73-9.99 mm; median 9.33 mm; P < .01). Preoperatively bent CPTi (range = 1.04-1.71 mm; median = 1.39 mm; P < .01) and intraoperatively bent CoCr (range = 1.11-2.11 mm; median = 2.01 mm; P < .01) rods underwent the least amount of shape loss. Conclusion: CPTi spinal rods bent after autoclave may lead to considerable loss of alignment correction. In addition, our results suggest that preautoclave bent CPTi and CoCr spinal rods bent after autoclave may be a more ideal choice of implant because they may provide more resistance to shape loss over time.